Managing natural resources for nurses in primary care - Santos, Débora Aparecida Silva; Silva, Fernanda Pereira da; Silva, Michele Salles da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
It is a quantitative, descriptive, not documentary research, field, and simple random sampling aimed to analyze the management of natural resources by the primary care nurse in a municipality in the state of Mato Grosso, MT in 2013. The sample consisted of 28 nurses asked about the influence of the environment on population health. The results showed that 92.86% of respondents perceive that relationship; whereas 71.43% and 60.71% of nurses assistants perform practices on environmental health activities in the units. The most cited actions were lectures in units or in schools; individual counseling or group; task forces or trawlers. It is hoped that with this research it is possible to generate a reflection on the role of nurses in the management of natural resources and expand the view of the health and environment in primary health care.